2021
DOI: 10.1021/acsenergylett.1c00594
|View full text |Cite
|
Sign up to set email alerts
|

Improved Li+ Transport in Polyacetal Electrolytes: Conductivity and Current Fraction in a Series of Polymers

Abstract: Polymer electrolytes mitigate safety concerns surrounding flammable liquid electrolytes in lithium-ion batteries. Poly(ethylene oxide) (PEO) electrolytes demonstrate viable conductivity values (∼1 × 10 −3 S/ cm) at elevated temperatures (>70 °C) but a relatively low Li + current fraction (≤0.2) because strong Li + coordination inhibits cation mobility. We have developed a series of polyacetal electrolytes by systematically varying methylene oxide (MO) and ethylene oxide (EO) units in the polymer backbone. Thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
51
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(54 citation statements)
references
References 28 publications
(38 reference statements)
3
51
0
Order By: Relevance
“…Amongst the various polymer chemistries investigated for SPE application, those comprising of polyethylene oxide (PEO) with various lithium salts have undoubtedly received the most interest, however recent studies of similar polyethers and polyacetals have also been reported by Balsara and Coates. 9–13 Despite high ionic conductivity ( ca. 10 −3 S cm −1 at 70 °C) above the melting temperature of PEO, poor room temperature performance, high crystallinity and low lithium transference numbers (typically around 0.2) of PEO-based SPEs remain a limitation to their practical implementation.…”
Section: Introductionmentioning
confidence: 99%
“…Amongst the various polymer chemistries investigated for SPE application, those comprising of polyethylene oxide (PEO) with various lithium salts have undoubtedly received the most interest, however recent studies of similar polyethers and polyacetals have also been reported by Balsara and Coates. 9–13 Despite high ionic conductivity ( ca. 10 −3 S cm −1 at 70 °C) above the melting temperature of PEO, poor room temperature performance, high crystallinity and low lithium transference numbers (typically around 0.2) of PEO-based SPEs remain a limitation to their practical implementation.…”
Section: Introductionmentioning
confidence: 99%
“…), defined as the fraction of ionic current carried by the cation relative to the solvent velocity in an electrolyte of uniform composition [2]. Recognition of the importance of this transport parameter dates back to Hittorf [3,4]; more recent work has emphasized the relevance of the cation transference number to the electrochemical efficacy of the electrolyte under fast charging conditions [8][9][10] and circumstances that lead to lithium dendrite growth [11,12]. Newman's concentrated solution theory can be used to relate 𝑡 ! "…”
mentioning
confidence: 99%
“…Consequently, we envisioned that the cationic copolymerization of cyclic acetals with anhydrides would be a novel way to produce polyesters. Of note, we can readily produce cyclic acetals on a large scale using common industrial feedstocks of formaldehyde and diols [39] …”
Section: Methodsmentioning
confidence: 99%